Corrigendum: tracing the origins of the Pituitary Adenylate-Cyclase Activating Polypeptide (PACAP) - Cardoso, João CR (2020)
A Corrigendum on Tracing the Origins of the Pituitary Adenylate-Cyclase Activating Polypeptide (PACAP) by Cardoso, J. C. R., Garcia, M. G., and Power, D. M. (2020). Front. Neurosci. 14:366. doi: 10.3389/fnins.2020.00366 In the original article, there was amistake in the legend for Table 1 as published. The table describes nomenclature for both vertebrates and non-vertebrates. In the original article, there was a mistake in Table 1 as published. PACAP receptor nomenclature for teleost and Actinopterygii (non-teleost) has errors. The Agnathan PACAP Receptor Gene/transcript should not be Adcyap1r1. During production, PACAP peptide column was erroneously positioned under the PACAP receptor. The corrected Table 1 and legend appears below. The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated.